Gender and performance anxiety in upper secondary dual-career sports programs in Iceland. - Þórey Björk Eyþórsdóttir 2001- (2023)
Anxiety is experienced by athletes at almost every level of performance and is therefore a common emotional state. The study aimed to examine gender and performance anxiety in upper-secondary dual-career sports programs in Iceland. Previous studies showed that females tend to have more anxiety than men. Dual-career involves the challenge athletes have when they are trying to have a career in sports but have to do that alongside studies or work which can cause anxiety. A sample of 194 athletes (129 males and 64 females) aged between 16 and 19 years participated in the study. A Sport Anxiety Scale-2 (SAS-2) and Test of Performance Strategies (TOPS) were used in the current study. Independent sample tests were used in the study to compare genders, if participants were in a team or individual sports, trust in the coach, and parental support. The results of this current study showed that females experience more sport anxiety than males, individual athletes have more sport anxiety, athletes that don’t trust their coach have more sport anxiety and those athletes that don ́t have parental support have more sport anxiety. Keywords: sport anxiety, gender, performance, type of sport, trust in the coach, parental support Nær allt íþróttafólk upplifir einhvern kvíða í sinni íþróttaiðkun og hann er í raun algengur meðal þess hóps. Markmið rannsóknarinnar var að kanna kynjabundinn mun á frammistöðukvíða hjá nemendum á íþróttaafrekssviðum framhaldsskóla á landinu. En fyrri rannsóknir sýna að konur í íþróttum eru almennt kvíðnari en karlar. Íþróttaafrekssviðin eru ætluð framhaldsskólanemendum sem leggja stund á íþróttir og veitir þeim stuðning til að sinna bæði námi samhliða íþróttum og það getur valdið kvíða. Úrtak rannsóknarinnar voru 194 nemendur á íþróttaafreksbrautum (129 karlar og 64 konur) og voru þau á aldrinum 16-19 ára. Nemendur svöruðu spurningalista sem innihélt sjálfsmatskvarða Sport Anxiety Scale-2 (SAS-2) og próf á frammistöðuaðferðum Test Performace Strategies (TOPS). Notast var við Independent samples tests ...